Control of pulsatile insulin secretion in man. - Matthews, DR; Lang, D; Burnett, M; Turner, R (1983)
Plasma insulin and glucose concentrations were examined in man in a basal state from central venous samples taken at 1-min intervals for up to 2.5 h. Normal subjects have insulin oscillations of mean period 14 min (significant autocorrelation, p less than 0.0001) with changes in concentration of 40% over 7 min. The pulsation frequency was stable through cholinergic, endorphin, alpha-adrenergic or beta-adrenergic blockade, or small perturbations with glucose or insulin. Stimulation of insulin secretion by intravenous glucose, tolbutamide or sodium salicylate increased the amplitude of the insulin oscillations while the frequency remained stable. Patients with a truncal vagotomy or after Whipple's operation had longer-term oscillations of 33 and 37 min periodicity (autocorrelation: p less than 0.0001), with insulin-associated glucose swings four times larger than those of normal subjects. Type 2 (non-insulin-dependent) diabetic patients had a similarly increased insulin-associated glucose swing of six times that seen in normal subjects. The hypothesis is proposed that the 14-min cycle of insulin production is controlled by a 'pacemaker' which assists glucose homeostasis. The longer 33-37-min oscillations, seen in those with denervation, may arise from a limit-cycle of the feedback loop between insulin from the B cells and glucose from the liver. The vagus may provide hierarchical control of insulin release.